Determination of the main intestinal parasites in dogs of Housing Units and Parks in Apizaco, Tlaxcala, Mexico - Chalco-Torres, Lorena Elizabeth; Guerrero-Lopez, Ana Elizabeth; Sanchez-Prado, Robert Gustavo; Perez, Jhonny Edgar; Oliveira, Claudio [UNESP]; Gomez, Juan Antonio; Lenin-Aguilar, Fernando; Nirchio-Tursellino, Mauro (Univ Zulia, Facultad Ciencias Veterinarias, 2023)
The bond between dogs and humans is a complex and multidimensional phenomenon, which, in addition to being biological, is social and becomes a Public Health problem. The concept of a pet owner has evolved to the term guardian, due to the relationship between people and dogs, who also have rights and are protected by international animal protection laws. The objective of the work was to analyze the handling of feces and evaluate the presence of helminths in the Housing Units and Recreational Parks (HU&RP) of Apizaco, Tlaxcala, Mexico. A descriptive cross-sectional study was used. Seventy five percent of people with dogs collect feces in bags and deposit them in garbage cans. There were significant differences (P<0.05) in the presence of parasites, 66% of dogs with tutors and 89% dogs without tutor. The identified parasites were Toxocara canis, Ancylostoma caninum, Cystoisospora and Uncinaria stenocephala. Dogs without tutor were the most parasitized 90% (P<0.05), prevailing T. canis(36%) and A. caninum(56%). It was found that the dogs with a guardian and access to public roads presented T. canis (73%) and A. caninum (77%). Dogs with a guardian without access to public roads had: 49% T. canis and 15% A. caninum. Unowned dogs were associated (P= 0.046) with a higher number of intestinal nematodes. In conclusion, in the HU&RP in Apizaco, Tlaxcala, there is a problem of handling dog excreta, which, when exposed, are the cause of zoonosis due to parasites, which shows the need for a comprehensive public health program towards a responsible dog ownership, which encompasses all sectors of society.
Keywords: Domestic dogs; intestinal parasites; feces